The interrogation of the OLAP CUBE by using multidimensional analyses - Robert Gabriel DRAGOMIR (Annals of Spiru Haret University Economic Series, 2011)
The present paper proposes to speak about the interrogation of the OLAP cubes, by using the multidimensional analyses. The first part of the paper deals with the dynamics of the business environment, a fact which triggers the necessity of the informatics systems for decision assistance. The second point of the paper is the presentation of the online analytical processing (OLAP). Connected to this point is the declarative interrogation language MDX, which assures the access to the OLAP interrogation, functions, offering us the possibility of defining the calculated members of the dimensions. A few examples show us how they work. In the end, we draw the conclusions, stressing the importance and the benefits of the intelligent solutions.